Kinetics of Hg and Pb Removal in Aqueous Solution Using Coal Fly Ash Adsorbent - Eko Prasetyo Kuncoro; Mochammad Zakki Fahmi (IPTEK Journal of Proceedings Series, 2014)
The objective of this research was to investigate the kinetics aspect of Hg and Pb adsorption using coal fly ash. A series of a Hg and Pb adsorption experiment using coal fly ash with contact time variation was carried out. The results were plotted to pseudo first order kinetic, pseudo second order kinetic and intra-particle diffusion model. High values of R2 were obtained from the plots of kinetics model for both heavy metals investigated, these values exceeded 0,8. The conclusion obtained was that Hg adsorption kinetics followed pseudo second order kinetic model while Pb adsorption kinetics followed intra-particle diffusion.